Wuji Pill and Akkermansia muciniphila alleviates intestinal dysfunction and depression-like behavior in irritable bowel syndrome through the microbiota-gut-brain axis - Li, Mengting; Xiao, Shuiming; Wang, Yanli; Li, Tao; Hu, Qin; Dong, Lijinchuan; Guo, Yuxuan; Shi, Zhe; Yang, Qing; Cai, Weiyan; Li, Qi; Peng, Bo; et al. (Frontiers in Microbiology, 2026)
IntroductionIrritable bowel syndrome (IBS) is a typical disorder of gut-brain interaction (DGBI). The microbiota-gut-brain (MGB) axis is pivotal in preventing and treating IBS. Wuji Pill is a traditional Chinese medicine commonly used to treat IBS. This study aimed to investigate the mechanism by which Wuji Pill improves IBS via the MGB axis.MethodsThe visceral sensitivity and colonic motor function were evaluated using the abdominal wall withdrawal reflex test and the colonic motility curve. Depression-like behavior were evaluated using sucrose preference test, open field test, novelty-suppressed feeding test, and forced swimming tests. The intestinal mucus secretion and the activation status of microglia was detected using AB-PAS staining and immunofluorescence staining, respectively. The species composition and abundance of gut microbiota were detected through 16S rRNA sequencing and RT-qPCR. Targeted metabonomics and RT-qPCR were used for metabolites and metabolic enzymes analysis.ResultsIn this study, Wuji Pill improved the symptoms of IBS rats and increased the relative abundance of Akkermansia muciniphila in feces. Additionally, antibiotics affected the repair of intestinal mucus secretion and significantly reduced the level of short-chain fatty acids. Subsequently, fecal microbiota transplantation and A. muciniphila transplantation can improve the symptoms of IBS rat by increasing intestinal mucus secretion, elevating the levels of acetic acid and butyric acid in feces. Additionally, the microglia in the cortex were suppressed, and the tryptophan-kynurenine pathway in the hippocampus was inhibited, leading to the conversion of tryptophan into 5-HT.DiscussionThis study highlights the Wuji Pill may alleviate IBS symptoms by modulating A. muciniphila and regulating the tryptophan metabolism pathway through MGB axis.